Mapping and Analysis of the Effect of Noise on Auditory and Non-Auditory Disorders Among Workers at the PMKS Produc-tion Station of PT. Sisirau - Amri Amri; Cut Ita Erliana; Nurjannah Nurjannah (Malikussaleh University, Aceh, Indonesia, 2025)
PT. Sisirau Palm Oil Mill Company is engaged in the production of crude palm oil (CPO) and kernel. In its production processes, the company continuously operates heavy machinery around the clock. These machines generate high noise levels, potentially causing both auditory (hearing-related) and non?auditory (communication, physiological, psychological, and work?productivity) disturbances among workers. This study aims to map the noise levels and analyse their impact on auditory and non?auditory disorders among workers at the production workstations of PT. Sisirau’s palm oil mill. Measurements were taken at 74 points across five production workstations: the kernel station, boiler station, engine room, clarification station, and press station. Using a Sound Level Meter, noise measurements were converted into equivalent continuous sound levels, followed by regression analysis employing the t?test to determine the relationship between noise exposure and worker disturbances. The results show that most measurement points at the production workstations exceeded the established Threshold Limit Value (TLV), with an average noise level of 98?dB. This indicates that noise levels in production areas are very high and require immediate reduction measures. Moreover, the statistical analysis revealed a significant correlation between noise levels and both auditory and non?auditory disturbances among workers (P-value = 0.002 0.05). In other words, as noise exposure increases, so does the risk of hearing impairment, communication problems, physiological and psychological effects, and reduced work productivity. These findings underscore the urgent need for noise control efforts, improvements to the working environment, and the implementation of more effective and consistent occupational health and safety policies to safeguard the health and safety of workers at PT. Sisirau’s palm oil mill.